Popper and the theory of scientific progress - Hanuszewicz, Stanisław (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2011)
We analyse the position of David C. Stove who accuses Popper, Kuhn, Feyerabend and Lakatos of being irrationalists. We concentrate on the subject whether this accusation is correct as far as Popper is concerned. In Stove's opinion, putting some words - like 'knowledge', 'discovery' or 'solution of a problem' - into quotation marks is irrational because our knowledge constantly grows, and we know more and more. Stove's position should be qualified as a foundationalism. He refuses Popper's fallibilism and, for this reason, cannot accept the view that all our knowledge is tentative and hypothetical. From the critical rationalism point of view, although our knowledge progresses, we are not justified in believing that we possess safe foundations for our knowledge, just because there are no such foundations. This position justifies our putting some success-words into quotation marks. If we accept fallibilism, formulated within framework of critical rationalism, there are good reasons for the neutralization procedure.